Fundamentos fisiopatológicos de la cirugía en diabetes mellitus tipo 2 - Molina F., Juan Carlos; Lanzarini S., Enrique (Revista Hospital Clínico Universidad de Chile, 2012)
Bariatric surgery is the only effective treatment for morbid obesity. Also, bariatric procedures have shown excellent results in controlling disorders of the glucose metabolism, improving glycemic control in diabetic patients and achieving remission in 48 to 98% of them. These results are better after surgeries with a malabsorptive effect, such as gastric bypass rather than purely restrictive procedures. In these patients, this improvement in glucose metabolism is observed after a short period of time after surgery, before a substantial weight lost is achieved. This phenomenon suggest that this effect is independent of weight lost and decreased food intake and there are other mechanisms that explain it. This article explains briefly some theories to understand these mechanisms.